Whose Sacrifice Is It, Anyway? The Rise and Fall of the Binding Father in the 1950s - Feldman, Yael S. (MiKAN, 2008)
"With our own hands we have murdered you," Liova Shamir, the bereaved father of Elik, wrote in 1948. Within a decade, his son Moshe declared that "Isaac is a passive object of the experiment", while his peer S. Yizhar had his 1948 hero proclaim: "I hate father Abraham for going to bind Isaac". Half a century later it is time to investigate the "first sons" of the Zionist revolution, especially their slowly evolving use of the "Aqedah" and other sacrificial narratives as tropes for their own ideological predicaments. Based on my forthcoming study. On the Cusp of Christianity: Rewriting Isaac in Tel Aviv, this article analyzes the role of several frames of reference — from Jewish post-biblical traditions and Kierkegaard's Fear and Trembling, to 19th-century Russian radicalism, Freudian psychology, and the Hebrew Crusade Chronicles— in shaping the discourse on sacrifice in Israel's most "Zionist" period, its first decade. It argues that these perspectives were employed by the authors of the "Palmach generation" in a dual process, one that signaled both a critique of sacrifice and a psychological defense against such critique. This 1950s defense, which sought to present Jewish / Zionist sacrifice as morally different and historically justifiable, no less than the critique that had triggered it, ultimately culminated in the contemporary debate between the upholders and rejecters of the Zionist (but also traditionally Jewish) position toward the "Aqedah", the "Binding" of Isaac.